MOTIVASI SISWA DALAM PEMBELAJARAN SEJARAH DI SMAN 2 KOTO XI TARUSAN - Roza, Anggia Mustika (Pendidikan Sejarah, 2014)
Purpose of the research is to know students motivation in learning History. Kind of researchÂ that research use is qualitative research. In this research, to take the informan the reseqrcher use purposive sampling teqhniqve. The informan are Hadnaster, Vice Headinaster , Theacher of history subject and the students of XI IPS 1 at SMA N 2 Koto XI Tarusan. The analysis of data making reduction.The research finding is learning motivation of the students is seen from learning ac truity of the students .Most of the students are not pay attention to the teacher explanation, geowse of the teacher explanation do not use variation method, the teacher almost use public speaking methode so the students is bored , based on the date above the researcher condude is pay attention to teacher explanation about first third meeting 10 person (33,25%) , Second meeting 12 % (38,70%), third meeting 10% (25,80),forth meeting (41,93%) and the last meeting (48,38%).Student motivation is seen pron reading artivity in reading activity the students are in low category.Based on information bafore the researcher ranclude that first meeting 25(73,52%), second meeting (57,14%), third meeting(32,25%), foorth meeting(35,48%)and the last meeting is students (42,85%).